THE GENETIC DIVERSITY OF MAIZE INBRED LINES GROWN IN IRAQ USING SIMPLE SEQUENCE RECURRENT (SSR) MARKERS - Alaa K.H. Al-Hazemawi,; Dhia S. Hassawi,; Abbas A. mohammed, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was conducted to determine the genetic variability among maize inbred lines grown in Iraq by using Simple Sequence Recurrent (SSR) markers. For estimating the genetic relationships, 10 SSR primers were used with 10 maize inbred lines. Two hundred and sixteen alleles (bands) with a range of 13 to 41 were identified for the SSR loci. Polymorphism information content (PIC) of the 10 SSR loci ranged from 0.60% to 100%. Primers ‘umc1566’, ‘umc1542’, and ‘umc2189’ showed the maximum PIC value; by contrast, ‘umc2225’showed the lowest PIC value. The 10 maize inbreds were clustered based on the matrix of genetic similarity using the UPGMA algorithm. Cluster analysis placed the inbreds lines in three clusters based on SSR data. The studied inbreds lines divided to groups and subgroups with cluster analysis that revealed agreement with their geographical origin. The results indicated that SSR marker has a high degree of polymorphism that allows efficient identification of maize genotypes, and this could be used in determining their heterotic groups.